Importancia de la valoración de hierro sérico, hemoglobina, hematocrito e índices hematimétricos para determinar la incidencia de anemia ferropénica en niños de 0 a 3 años que acuden al hospital pediátrico “alfonso villagómez román” de la ciudad de riobamba durante el período que comprende desde el mes de diciembre de 2010 hasta febrero del 2011 - Narváez Campos, Rosa Elizabeth (2011)
In the capital city of Riobamba Chimborazo province, works Pediatric Hospital "Alfonso Villagómez Roman" with medical care across multiple services to low income people in which includes clinical laboratory services is made the main areas such as reception area samples coprology and Urinalysis, Blood Chemistry, Hematology, Microbiology and Area Bodega and Archives.